PROPOSED BUSINESS STRATEGY ON THE ONLINE DELIVERY SERVICE PLATFORM SHOPEEFOOD - Rahajeng Widiana Purwaningrum; Mohammad Hamsal (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Online food service delivery platform should be essential to improve the growth journey and create more benefits to culinary business owners. They have other challenges to provide the right solutions to various different segments, especially MSMEs (Micro, Small and Medium Enterprises). MSMEs have limitations in terms of digital literacy. In this study, the authors use the AFI framework (Analysis, Formulation, and Implementation) with a case study of determining ShopeeFood's business strategy through quantitative research by distributing questionnaires to respondents and finding difficulties and advantages for culinary business owners or merchants in registering and using online food service platforms. The results show that online food delivery system platform ShopeeFood has gained positive response in order to create benefits for merchants, especially MSME in helping their business growth but still need to improve especially for merchant journey. The strategy towards merchant journey especially MSME can be addressed by product improvement, marketing expansion and brand strengthening. The product improvement will deliver a better journey for merchants to register the platform and use the application.